Comparing CPT Results and Numerical Method Investigations to Assess the Behaviour of Pile and Sand and Mixed Soil Using ABAQUS - Yadak, Reza (Curtin University, 2020)
The cone penetration test (CPT) is a method used to determine the geotechnical engineering properties of soils and delineating soil stratigraphy. This study demonstrates the expansion of numerical models using ABAQUS software, which are purposed to be used to predict the load-settlement and the ultimate bearing capacity behavior of pile foundations embedded in sand and mixed soil. This achieved by validating numerical results, using ABAQUS, and CPT site investigations.